The Components of Dengue Haemorrhagic Fever (DHF) Surveillance System in Health Department of Kediri City - Binti Mahfudhoh (Universitas Airlangga, 2015)
Dengue Hemorrhagic Fever (DHF) is an infectious disease that can cause death. The 2013 incidence rate (IR) of DHF in Kediri City was 99.28 per 100,000 population with a mortality rate (CFR) of 0.73%. One of the efforts to control DHF in Kediri City is implementing an epidemiological surveillance system. This study aims to evaluate the implementation of DHF surveillance in the Kediri District Health Office. This research uses a descriptive method with a cross-sectional design. Respondents are executors of the DHF surveillance program in the health department. Data sources are primary data and secondary data. The results showed that the component of DHF surveillance data collection is routine and non-routine, adequate personnel, and means of surveillance, active, and passive data collection methods. Frequency of data collection every month, quarterly, and incidental. Timeliness cannot be calculated, completeness of data is 47.9% and forms are sufficient. Data compilation based on people, time, place, and endemicity of the region. Data analysis is based on morbidity, mortality, and regional stratification data. Data interpretation includes comparative analysis, coverage, and trends. Epidemiological information in the form of general information on DHF. Disseminate information in the form of DHF reports to the East Java Provincial Health Office and feedback to the Public Health Center (PHC). The implementation of DHF surveillance in the Kediri District Health Office based on the surveillance component is still not in accordance with the DHF control module and guidelines for implementing a health epidemiology surveillance system.